Fiscal Issues in Financial Crisis - Vladimir Gligorov (The Vienna Institute for International Economic Studies (wiiw), 2011)
Fiscal constraint is potentially lax in catching-up economies, but it has not been abused by most countries considered in this paper. Fiscal risks are significant currently, but sustainability and structural balances are not threatened as a rule, if the return to potential growth rates is to be achieved in the medium run. The risks to countercyclical public financing could be discouraged by a comprehensive EU stabilization policy of some sort. Early euro adoption, absent credible stabilization policy, is not the first best policy option for fiscal policy targets.
Keywords: E62; G18; 330; public debt; sustainability; No-Ponzi game criterion; private debt; foreign debt